2012
DOI: 10.1364/ao.51.003655
|View full text |Cite
|
Sign up to set email alerts
|

150 W high-average-power, single-frequency nanosecond fiber laser in strictly all-fiber format

Abstract: We demonstrate an all-fiber, single-frequency nanosecond laser with both high peak power and average power based on a master oscillator power amplifier (MOPA) configuration. The MOPA produced a single-frequency pulsed laser with pulse duration of ∼8  ns. The average and peak power were as much as 139.3 W and 1.07 kW, respectively, when the repetition rate was 10 MHz, and 153.1 and 668 W, respectively, when the repetition rate was 20 MHz. Higher output power can be obtained by increasing pump power of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The peak power of the ns pulses can be calculated as [21] where is the normalized intensity of the ns pulses, and is pulse period. is the average power, and is the repetition frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The peak power of the ns pulses can be calculated as [21] where is the normalized intensity of the ns pulses, and is pulse period. is the average power, and is the repetition frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Fang et al [18] and Liu et al [1] have demonstrated narrow-linewidth pulses by employing a fiber pigtailed intensity modulator. Since it is difficult to obtain high power narrow-linewidth pulses directly from an oscillator, a master oscillator power amplifier (MOPA) structure was always employed [1,[16][17][18][19] . Zhu et al have obtained ∼80 ns pulses with pulse energy of 220 µJ and repetition rate of 20 kHz from an all-fiber MPOA [16] , and Fang et al generated 15 ns pulses with peak/average power of 33 kW/2.5 W [18] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] have demonstrated narrow-linewidth pulses by employing a fiber pigtailed intensity modulator. Since it is difficult to obtain high power narrow-linewidth pulses directly from an oscillator, a master oscillator power amplifier (MOPA) structure was always employed [1, 1619] . Zhu et al.…”
Section: Introductionmentioning
confidence: 99%
“…The pulse series can also be modulated as macro-micro pulses, which are widely used in guide star systems [1,3]. Su et al [11] reported an all-fiber 1064 nm laser that has over 100 W output with about a 8 ns pulse duration and a 20 MHz repetition rate. The system used a single-frequency CW laser as the master oscillator (MO).…”
Section: Introductionmentioning
confidence: 99%